Measurement of Plasma Unbound Unconjugated Bilirubin - Ahlfors, Charles E. (Analytical biochemistry, 2000)
A method is described for measuring the unconjugated fraction of the unbound bilirubin concentration in plasma by combining the peroxidase method for determining unbound bilirubin with a diazo method for measuring conjugated and unconjugated bilirubin. The accuracy of the unbound bilirubin determination is improved by decreasing sample dilution, eliminating interference by conjugated bilirubin, monitoring changes in bilirubin concentration using diazo derivatives, and correcting for rate-limiting dissociation of bilirubin from albumin. The unbound unconjugated bilirubin concentration by the combined method in plasma from 20 jaundiced newborns was significantly greater than and poorly correlated with the unbound bilirubin determined by the existing peroxidase method (r = 0.7), possibly due to differences in sample dilution between the methods. The unbound unconjugated bilirubin was an unpredictable fraction of the unbound bilirubin in plasma samples from patients with similar total bilirubin concentrations but varying levels of conjugated bilirubin. A bilirubin-binding competitor was readily detected at a sample dilution typically used for the combined test but not at the dilution used for the existing peroxidase method. The combined method is ideally suited to measuring unbound unconjugated bilirubin in jaundiced human newborns or animal models of kernicterus.